Jordlöparfaunan i bestånd av contortatall (Pinus contorta) och svensk tall (P. sylvestris) 1987 och 2010 - Borgstrand, Emma; Videkull, Li (2013)
In the 1970´s the North American lodgepole pine (Pinus contorta) was introduced to Sweden in large scale. The lodgepole pine affects its new environment different from Scots pine (P. sylvestris), leading to a change in biological diversity. Forestry today affects the ground beetle fauna (Carabidae). Habitat specialists associated with older forests are first affected. When the canopy closes again after a clear-cutting species that prefer open habitats reduces and those who prefer mature/closed forests increase. In this study we compare differences in diversity and community structure of ground beetles in stands of lodgepole pine and Scots pine. We also compared if the patterns changed between 17-18 year old stands and 39-40 year old stands. The long time interval in the study was unique. Ground beetles were collected in four sites in northern Sweden where stands of lodgepole pine and Scots pine were planted adjacent to each other. The various species of ground beetles were divided into three functional groups 1) generalists, 2) open habitat species, and 3) forest species. In our study, the species diversity in stands of lodgepole pine was slightly lower than in stands of Scots pine according to Fisher's alpha. Calathus micropterus was the most common species in both years. In 1987 it was most common in stands of lodgepole pine and 2010 in stands of Scots pine. Calathus micropterus is a shadow demanding forest species which explains why it was more common in 1987 in the more closed stands of lodgepole pine and 2010 in the unmanaged stands of Scots pine. 1987, Amara nigricornis and Amara lunicollis were among the most common species, but they were not found 2010. These species prefer open, dry and hot bare surfaces which may be one reason why the species was not found in 2010 when stands were older and the canopy more closed. Our results shows that if no more species adapt to the new habitats that stands of lodgepole pine creates the future introduction of lodgepole pine may pose threats to the ground beetle ...